Lactase can target cellular differentiation of Acanthamoeba castellanii belonging to the T4 genotype - Fathimah, Afaaf Simau; Usman, Ahmed *; Khan, Khalid Mohammed; Khan, Naveed Ahmed; Siddiqui, Ruqaiyyah; Alharbi, Ahmad M; Alfahemi, Hasan; Ayaz, Anwar * (Springer Verlag, 2024)
The free living Acanthamoeba spp. are ubiquitous amoebae associated with potentially blinding disease known as Acanthamoeba keratitis (AK) and a fatal central nervous system infection granulomatous amoebic encephalitis (GAE). With the inherent ability of cellular differentiation, it can phenotypically transform to a dormant cyst form from an active trophozoite form. Acanthamoeba cysts are highly resistant to therapeutic agents as well as contact lens cleaning solutions. One way to tackle drug resistance against Acanthamoeba is by inhibiting the formation of cysts from trophozoites. The biochemical analysis showed that the major component of Acanthamoeba cyst wall is composed of carbohydrate moieties such as galactose and glucose. The disaccharide of galactose and glucose is lactose. In this study, we analyzed the potential of lactase enzyme to target carbohydrate moieties of cyst walls. Amoebicidal assessment showed that lactase was ineffective against trophozoite of A. castellanii but enhanced amoebicidal effects of chlorhexidine. The lactase enzyme did not show any toxicity against normal human keratinocyte cells (HaCaT) at the tested range. Hence, lactase can be used for further assessment for development of potential therapeutic agents in the management of Acanthamoeba infection as well as formulation of effective contact lens disinfectants.